Comparison of Endoscopic Findings with Gastroesophageal Reflux Disease Questionnaires (GerdQ) and Reflux Disease Questionnaire (RDQ) for Gastroesophageal Reflux Disease in Medan - Gontar Alamsyah Siregar; Sahat Halim; Ricky Rivalino Sitepu (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2015)
Background: There are many questionnaires that have been developed to diagnose gastroesophageal reflux disease (GERD), i.e. reflux disease questionnaire (RDQ), and the recently developed, gastroesophageal reflux disease questionnaires (GerdQ). In this study, we tried to compare GerdQ and RDQ in terms of sensitivity and specificity to diagnose GERD and its relationship with endoscopic findings.Method: This study was a cross sectional analytical study. Subsequently, all the subjects were evaluated using the GerdQ and RDQ, then underwent esophagogastroduodenoscopy examination. The severity of endoscopically observed reflux esophagitis was graded with the Los Angeles classiﬁcation. All endoscopy was performed by well-trained doctor.Results: A total of 85 patients were examined, 34 (40%) patients had reflux esophagitis at endoscopy examination, including 15 (44.1%) cases of grade A, 11 (32.3%) cases of grade B, 4 (11.8%) cases of grade C, and 4 (11.8%) cases of grade D. Analysis study using sensitivity, specificity, and receiver operating characteristic (ROC) test showed that GerdQ had sensitivity (49%), specificity (91%), and an area under the ROC of 0.701 (p value = 0.002). RDQ had sensitivity (24%), specificity (91%), and an area under the ROC of 0.574 (p value = 0.253). Taking 11 as the cut off point for GerdQ, a maximal sensitivity of 73.5%, specificity of 82.4%, and an area under the ROC of 0.779 was achieved.Conclusion: GerdQ and RDQ can be used to help diagnose GERD, but GerdQ is more superior than RDQ in diagnosing GERD. A multi-center study with larger samples is needed to determine the best GerdQ’s cut off point in Indonesia.